Phytoalexins stimulation in the infected Sesamum indicum L. with fungus Macrophomina phaseolina (Tassi) Goid (Rot Disease) - Sharma, Sandhya; Sharma, Vinay; Alam, Afroz (International Journal of Environment, 2015)
Plants respond to a wide variety of pathogen attack. They show the local response in originally attacked plant organ and systemic response in unaffected plant parts with the de novo production of phytochemical compounds. Phenolics (polyphenols) play an important role in the defense mechanism of the plants. So, this study was carried out to analyze the metabolic modifications in Sesame plant after the infection with the pathogen (Macrophomina phaseolina) by estimating the levels of polyphenol in 7 days and 14 days old Sesame plants. The polyphenol contents in infected plants are considerably exceeded in contrast to control plants. This in vivo study of M. phaseolina infection reveals the differences of resistance levels in Sesame against the pathogen. The obtained results give important information concerning the plant-pathogen interactions, in the defense response for Sesame improvement programs seeking the adaptation to the diverse range of fungal attack along with adverse environmental factors.International Journal of Environment Vol.4(4) 2015: 1-18